2014
DOI: 10.1016/j.cub.2014.01.047
|View full text |Cite|
|
Sign up to set email alerts
|

TrkB-Mediated Protection against Circadian Sensitivity to Noise Trauma in the Murine Cochlea

Abstract: Summary Noise induced hearing loss (NIHL) is a debilitating sensory impairment affecting 10–15% of the population caused primarily through damage to the sensory hair cells or to the auditory neurons. Once lost, these never regenerate [1] and no effective drugs are available [2, 3]. Emerging evidence point towards an important contribution of synaptic ribbons in the long-term coupling of the inner hair cell and afferent neuron synapse to maintain hearing [4]. Here we show in mice (nocturnal) that night noise ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 39 publications
5
87
1
Order By: Relevance
“…Such factors could include the exact animal placement in relation to the sound source, the time of day the animal was exposed (Meltser et al, 2014), the exact amount of anesthetic that is absorbed into the blood, as well as all stress-related factors listed above. Even among heterogeneous genotypes of guinea pig and inbred strain mice the variability of ABR threshold shifts after unanesthetized AOE can be dramatic (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Such factors could include the exact animal placement in relation to the sound source, the time of day the animal was exposed (Meltser et al, 2014), the exact amount of anesthetic that is absorbed into the blood, as well as all stress-related factors listed above. Even among heterogeneous genotypes of guinea pig and inbred strain mice the variability of ABR threshold shifts after unanesthetized AOE can be dramatic (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF further regulates astroglial plasticity in the SCN in a circadian fashion, which plays a crucial role in synchronization processes of circadian rhythms (Girardet et al, 2013). In a recent study, we found that BDNF via its receptor TrkB, protects mice against the negative consequences of an acute acoustic stressor, acoustic noise trauma, and that mice were significantly more susceptible to noise stress in the night as compared to day (Meltser et al, 2014). Thus, the increased BDNF mRNA levels in the SCN and increased BDNF in plasma may represent neural adaptations that prevent stressinduced alterations in the SCN and, in turn, facilitate changes in adrenal ACTH sensitivity via a phase advanced PER2::LUC rhythm.…”
Section: Sdl Increases Bdnf In the Scn And Plasmamentioning
confidence: 98%
“…Ideally, even the time of exposure should be standardized in light of evidence that cochlear noise vulnerability appears subject to a diurnal cycle (Meltser et al 2014). In some studies, the goal may be unilateral NIPTS, so that an anesthetized animal may be positioned to only expose one ear (e.g., Longenecker and Galazyuk 2011;Turner et al 2012;Hickox and Liberman 2014).…”
Section: Unilateral Noise Exposure and Anesthesiamentioning
confidence: 99%